The frequency and type of graphical representations in science trade books for children. Issue 1 (2nd January 2016) - Coleman, Julianne M.; Dantzler, John A.
Abstract: This study sought to examine the frequency and type of graphical representations in science trade books for children from 1972 to 2007. Specifically questions addressed differences in graphical forms in science discipline and for intended audience age for books. The results revealed that there is an increase in the presence and variation of graphics over time. The physical science trade books had larger proportions of the range of graphics than life and earth science books. Most notably flow diagrams, cross sections, cutaways and tree diagrams were present in physical science books. Regarding intended audience age, there were more graphical representations of most types in books for intermediate age children. The results suggest that students will encounter a higher presence of trade books with graphics and graphical types in the coming years.